The Clinical Features of Co-circulating Dengue Viruses and the Absence of Dengue Hemorrhagic Fever in Pakistan - Erum Khan; Dhani Prakoso; Kehkashan Imtiaz; Faisal Malik; Joveria Q. Farooqi; Maureen T. Long; Kelli L. Barr (Frontiers Media S.A., 2020)
Dengue virus (DENV) is the most common and widespread arboviral infection worldwide. Though all four DENV serotypes cocirculate in nature, the clinicopathological framework of these serotypes is undefined in Pakistan. A cross-sectional, observational study was performed to document the circulation of various arboviruses in the Sindh region of Pakistan. Here we describe a population of patients diagnosed with DENV spanning a 2-year period. This study used an orthogonal system of NS1 antigen ELISA followed by RT-PCR for DENV detection and subtyping. A total of 168 NS1 positive patients were evaluated of which 91 patients were serotyped via RT-PCR. There was no significant difference between sex or age for infection risk and peak transmission occurred during the Autumn months. DENV2 was the most common serotype followed by DENV1 then DENV3, then DENV4. The data show that DENV1 patients were more likely to have abnormal liver function tests; DENV2 infected patients were more likely to exhibit arthralgia and neurological symptoms; DENV3 patients were more likely to complain of burning micturition and have elevated lymphocyte counts and low hematocrit; and DENV4 patients were more likely to report headaches and rash. Notably, no dengue hemorrhagic fever or other manifestations of severe dengue fever were present in patients with primary or secondary infections. We were able to identify significantly more NS1 antigen positive patients than RT-PCR. This study demonstrates that all four DENV serotypes are co-circulating and co-infecting in Pakistan.